Chemical and physico-chemical characterization of some Syrian traditional cheeses and its comparison with some similar international kinds - Harfouch, Muhssen (Latakia University Journal -Biological Sciences Series, 2013)
The aim of this research is to study chemical and physico-chemical characteristics of Akawi, Medaffarah, Shankalish and Sorkeh cheeses for their identification and comparison with some internationally widespread cheeses. Several chemical analyses were performed on samples collected from different region famous with these products. The study showed big variation in chemical composition of studied cheeses, and that Shankalish, and Medaffarah are semidry cheeses but Akawi and Sorkeh are soft one. Fates and proteins in Shankalish cheese were subject to advance enzymatic activity, ripening coefficient (37.9%) and free fattyacids (2.1%) were similar to the international Camembert and Roquefort cheeses. This study assi indicated that Shankalish is poor in fat and rich in protein (14.2% and 56.7% of dry basis respectively). The results showed that calcium and phosphor content in Akawi (0.64% and 0.55%of dry basis respectively ) was higher than (0.33% and 0.35%) in Medaffarah and (0.21% and 0.41%) in Shankalish. However, the contents of both cadmium and aluminum (0.2 mg/kg and 332.6 mg/kg respectively) in Sorkeh and Medaffarah respectively are very high and this may be a result of containers usually used in the processing.